2018
DOI: 10.1016/j.techfore.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phones, institutional quality and entrepreneurship in Sub-Saharan Africa

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 100 publications
4
47
0
Order By: Relevance
“…Political instability and the absence of violence gauge the depth of sponsored or unsolicited violence or terrorism. These measures of institutional quality agree with institution-centric literature (see Asongu and Nwachukwu 2016a, b;Asongu et al 2018b;Bankole et al 2015;Barasa et al 2017 for some examples).…”
Section: Data Sources and Measurementssupporting
confidence: 87%
“…Political instability and the absence of violence gauge the depth of sponsored or unsolicited violence or terrorism. These measures of institutional quality agree with institution-centric literature (see Asongu and Nwachukwu 2016a, b;Asongu et al 2018b;Bankole et al 2015;Barasa et al 2017 for some examples).…”
Section: Data Sources and Measurementssupporting
confidence: 87%
“…On the other hand, the impact of mobile phones or mobile Internet on social development or individual well-being has also received extensive attention from scholars [19]. There is quite an extensive amount of literature showing that mobile phone and/or mobile Internet use can reduce corruption [54,55], improve institutional quality [56], affect individual social networks [57], increase search convenience [46,58], etc. However, other studies have also found that excessive use of mobile phones can cause "technostress", which has negative effects on users' mental and physical health and work efficiency [59][60][61].…”
Section: Mobile Phone and Mobile Internetmentioning
confidence: 99%
“…This makes mobile payments deployment relevant to the growth and development of businesses across the world (Oliveira et al 2016). More importantly in developing countries, the mobile payment revolution is transforming households and businesses by providing a business solution to small and medium-sized businesses as well as mobile phone-related financial services to the underserved population, and help developing economies leapfrog poor non-existing payment infrastructure (Asongu et al 2018).…”
Section: Introductionmentioning
confidence: 99%